Corporate Governance of State-owned Enterprises: A Framework for Addressing Board Accountability Deficit in State-owned Enterprises - JENNINGS, DEIRDRE (Trinity College Dublin. School of Law. Discipline of Law, 2019)
Accountability is the quintessence of a successful corporate governance regime; it pushes a board act in the best interests of an SOE and ensures a board is responsible for its actions. This thesis highlights how accountability standards for boards of SOEs have failed to provide an adequate governance framework, which has resulted in an accountability deficit. The recommendations contained within this thesis sets out proposals for implementing a better regime to increase board accountability.
APPROVED
Keywords: Corporate governance; State-owned Enterprises